Pengaruh Beban Kerja dan Psychological Well-Being Terhadap Kinerja Karyawan CV. Riau Indo Makmur Indragiri Hilir Riau - Sehani Sehani; Trio Agung Prayetno; Rhonny Riansyah (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to determine the influence of workload and psychological well-being on employee performance at CV Riau Indo Makmur (RIM) in Indragiri Hilir, Riau. The research is motivated by the phenomenon of fluctuating employee absenteeism and the company’s achievement of targets, which are suspected to be related to workload and employees’ psychological well-being. The research method used is quantitative with a descriptive approach and multiple linear regression analysis. The sample consisted of 40 respondents. The results of the study indicate that workload has a significant partial effect on employee performance. Psychological wellbeing, however, does not have a significant partial effect on employee performance. Simultaneously, workload and psychological well-being together have a significant influence on employee performance.